Korelasi Hasil Pemeriksaan NLR ( Neutrophil Lymphocyte Ratio ) dan Albumin Pada Calon Tenaga Kerja Indonesia yang Positif Hepatitis B - Puspentarini, Desak Ayu; I Wayan Getas; Siti Zaetun; Pancawati Ariami (Poltekkes Kemenkes Mataram, 2025)
Background: Hepatitis B is a clinical or pathological syndrome characterized by varying degrees of inflammation and necrosis of the liver caused by Hepatitis B Virus (VHB). Liver biopsy examination is commonly performed in monitoring patients with HBK, but the cost of the examination is relatively expensive. Therefore, biomarkers that can be used to monitor the disease progressivity of Hepatitis virus infection are needed. One of the inflammatory markers that is easy to do is the Neutrophil Lymphocyte Ratio (NLR) value. In the state of viral hepatitis, albumin levels will decrease because albumin is the largest substance of protein produced by the liver. Objective:To Know the Correlation of Neutrophil Lymphocyte Ratio (NLR) and Albumin Test Results in Hepatitis B Positive Indonesian Migrant Workers Methods: This research is an analytical observational study with a cross sectional research design and a simple random sampling technique. Results: The sig p value of Albumin is 0.020 and NLR p value is 0.02, which means that sig p < α value (0.05), which means that H0 is rejected and H1 is accepted, meaning that there is a relationship between Neutrophil Lymphocyte Ratio (NLR) and Albumin levels in Indonesian labor candidates who are positive for Hepatitis B. Conclusion: Based on statistical tests, it was found that there was a negative correlation between the results of the Neutrophil Lymphocyte Ratio (NLR) and Albumin examinations in Hepatitis B Positive CTKI.